Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Highly dispersed Ni-Mo encapsulated in hollow mesoporous ZSM-5 as an efficient catalyst for tetralin conversion to light aromatics - Mengdi Wang; Limin Zhang; Haoqing Zhang; Jiaming Wu; Keyan Li; Xinwen Guo (Fuel, 2026)

Interpretable mapping of fine-grained urban building functions from street-view images using foundation models - Jiaming Sun; Wei Yang; Tingting Xu; Zongshun Tian; Yongchuan Zhang; Mengjia Yin (Computers, Environment and Urban Systems, 2026)

Impacts of carbon source type on metabolic pathways and microbial synergy in the simultaneous anammox and endogenous denitrification process - Wenlong Liu; Yuyan Zhang; Chenhao Yue; Jiaming Wang; Jun Li; Huijie Lu; Shilong He; Yongzhen Peng (Bioresource Technology, 2026)

Integrative genetic analysis reveals shared genetic architecture underlying coronary artery disease, CT-Defined coronary atherosclerosis, and cardiometabolic risk factors - Yao Zhao; Yingying Xie; Didi Wen; Jin Zhang; Ziliang Xu; Zhibin Wu; Jiaming Li; Yuanqiang Zhu; Minwen Zheng (Functional & Integrative Genomics, 2026)

Oxidative-stress-mediated apoptosis triggered by microplastics disrupts bovine oocyte maturation - Yu Wang; Jiaming Yue; Yijing Yin; Yan Zhang; Yi Zheng; Hao Jiang; Jiabao Zhang; Bao Yuan; Liang Shuang (Theriogenology, 2026)

Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

Constant-voltage triboelectric nanogenerator coupled with an intermittent speed-up mechanism and bionic jellyfish blades for low-speed water flow energy harvesting - Chenxi Li; Yongle Zhou; Fupu Xie; Jiaming Zhang; Yi Li; Hongwei Wang; Kaisheng Li; Zihao Li; Siyuan Liu; Tianyu Li (Chemical Engineering Journal, 2026)

Amphibian skin peptides: Diversity, biological functions, and research progress - Zihui Chen; Qing Pan; Jiaming Zhang; Ren Lai; Wenhua Yu; Aili Wang (Toxicon, 2026)

Sustainable urban transitions in resource-based cities: How transition willingness translates into external green technology acquisition - Jiachuan Liu; Peiyuan Zhang; Jiaming Li; Shuo Lu; Wenzhong Zhang (Sustainable Production and Consumption, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Study on the influence of different cold shock methods on the mechanical properties and rockburst proneness of high-temperature monzogranite - Jiaming Li; Xinyu Liu; Shuguang Zhang; Shibin Tang; Xiang Huang; Wenbo Liu (Engineering Geology, 2026)

A multifunctional photothermal nanoplatform integrating CD47 degradation and metabolic reprogramming for potentiated tumor immunotherapy - Jiaming Zhang; Chao Chen; Zhousheng Lin; Zeyu Liu; Juan Zhang; Jieying Qian; Xiaowan Huang; Yunjiao Zhang; Guangyu Yao (Chemical Engineering Journal, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Carbide-induced high dispersion and electronic regulation of Pt species toward stable propane dehydrogenation - Xiaonan Wang; Jiaming Ma; Jun Li; Haoyu Yan; Zhikai Yang; Bo Jiang; Xiao Zhang (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Microbes Isolated from Ailanthus altissima Leaves Contribute to Samia cynthia’s Tolerance to the Toxic Quassinoid Diterpenoid - Jiaming Zhang; Juan Hua; Yangyang Wang; Jiayi Liu; Zhen Yang; Yanqun Liu; Shihong Luo (Journal of Chemical Ecology, 2026)

Adaptive NN finite-time inverse optimized formation fault-tolerant control for multi-USV systems with actuator faults - Jiaming Zhang; Yi Zuo; Shaocheng Tong (Ocean Engineering, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

DCMArb: Decoupled-Collaborative Mamba for Arbitrary-scale Hyperspectral Super-resolution - Shuo Wang; Mi Wang; Jiaming Wang; Zhenbei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Electrochemically crosslinked poly(arylene ether sulfone)-triphenylamine electrochromic polymer networks for smart windows - Keying Feng; Zhen Xing; Xiangfu Shi; Jiaming Tian; Hao Zhang; Zong-Quan Wu; Zheng Chen; Zhenhua Jiang (Chemical Engineering Journal, 2026)

Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

Experimental study of condensation induced water hammer caused by the accumulation of condensate water in the steam pipeline - Minchao Liang; Jiaming Zhao; Jiarui Zhang; Rongyang Xue; Yili Yang; Wentao Guo; Shengfei Wang (Annals of Nuclear Energy, 2026)

Machine learning-assisted smartphone fluorescence sensing for ultrasensitive and point-of-care testing of acid phosphatase - Fusheng Zhong; Jiaming Zhang; Huaxi Ruan; Tonglong Yang; Jinbo Cao; Liangliang Peng; Jinhui Liu; Qingqing Deng; Li Wang (Analytica Chimica Acta, 2026)

Effects of renewable portfolio standards obligation distribution: Equilibrium analysis of supply side vs. demand side in power supply chain networks - Huan Zhang; Jiaming Wu; Sien Chen; Jianli Jiang (Utilities Policy, 2026)

How competition shapes energy efficiency in shared e-scooter systems - Yuhan Zhang; Jiaming Wu; Zhirui Ye; Maria Attard (Transportation Research Part D: Transport and Environment, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

Revealing the antioxidant potential of Artemisia integrifolia L.: Integrated discovery of bioactive compounds via UHPLC-DPPH and activation of the Nrf2/HO-1 signaling pathway - Huimin Li; Qian Gao; Yijin Wu; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Decoding the hidden resistome: Single-cell Raman detection of viable but non-culturable antibiotic-resistant bacteria in aquatic environments - Tong Zhou; Linyi Fan; Hao Yang; Jiaming Zhang; Jingshuang Cui; Jiao Qu; Ya-nan Zhang (Journal of Hazardous Materials, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Effects of microenvironmental factors on water-insoluble precipitation induced by soybean urease - Chongda Duan; Jiaming Zhang; Yi Luo; Yanzi Sun; Jiaxing Liu; Xiang Lv (Journal of Environmental Chemical Engineering, 2026)

The extract of Cirsium setosum exerts antimicrobial activities on largemouth bass infected by Aeromonas veronii via regulating inflammatory and antioxidant responses - Yuhuan Qiu; Chutong Zhang; Dekun Tang; Dasen Li; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Tailoring oxygen vacancy-rich NH4V4O10/porous carbon hierarchical structures for superior aqueous zinc-ion batteries - Yong Liao; Dui Ma; Qifan You; Hongtao Zhang; Jiaming Ni; Zhiqiang Xiong; Xiao Liang; Haitao Huang (Chemical Engineering Journal, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Transport Pathway Evolution and Retention Dynamics of Escherichia Coli in Homogeneous and Heterogeneous Porous Media - Yuanyuan Jia; Zhipeng Tu; Wenjing Zhang; Shutong Jiang; Jiaming Sun; Bo Wan (Transport in Porous Media, 2026)

Two-terminal ferroelectric memristors: material innovation, mechanistic breakthroughs, new opportunities for intelligent computing - Jiaming Zhang; Chaocheng Sun; Yan Jing; Yifei Pei; Jianbin Xu; Xiaobing Yan; Jianhui Zhao (Science Bulletin, 2026)

Generalized traverse task scheduling based on THRO algorithm for AUV with energy-constrained - Qixin Sha; Rui Nian; Jiaming Zhang; Xiaoting Xu; Yue Shen; Bo He (Ocean Engineering, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

Components with potential anti-inflammatory effect from the seeds of Dolichos lablab - Wei Zhang; Yijin Wu; Jiaming Cheng; Jingya Ruan; Yingying Wang; Lequan Yu; Dan Wang; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2026)

High Cholesterol Facilitates Ovarian Androgen Production and Contributes to the Development of Polycystic Ovary Syndrome - Yue Liu; Shourui Hu; Xiaofan Liang; Jiaming Zhang; Yiming Qin; Chunxuan Geng; Yuqing Zhang (Phenomics, 2026)

Nitrogen uptake preference of Avicennia marina and Aegiceras corniculatum in simulated saline water under varying salinities - Dejian Su; Jiaming Hu; Chutong Zhang; Yushuang Yang; Xiuru Zhu; Jian Guan; Yong Liu (Marine Environmental Research, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

Paeoniae Radix Rubra extract inhibits largemouth bass ranavirus (LMBV) replication by suppressing inflammatory response and oxidative stress - Yang Liu; Dasen Li; Wenyan Liu; Chutong Zhang; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Spatial mismatch and inequality between ecological pressure and economic benefits embodied in agricultural trade - Kaige Lei; Jiaming Zhang; Yan Li; Xinhui Feng; Jiayu Yang; Li Hou; Jianguo Liu (Environmental Impact Assessment Review, 2026)

Assessment of laterization degree of tropical residual laterites overlying carbonate rocks in Yunnan, China - Haiyan Gao; Zhongxin Deng; Zemin Xu; Yixi Wen; Jiaming Zhang; Jipu Chen; Lin Tian (CATENA, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

Tracking 3D desiccation crack evolution and permeability dynamics in expansive soil - Yun Peng; Jiaming Zhang; Yi Luo; Tianle Liu; Mingjian Hu; Shuai Liu (Bulletin of Engineering Geology and the Environment, 2026)

Evaluation of Groundwater Origin, Quality, and Potential Health Risks in the Ordos Coal Mine Base, Northwest China: Insights from Geochemical and Isotopic Approaches - Jiaming Zhou; Keyi Zhang; Tenglin Deng; Zilong Liao; Bing Xu; Fei Gao; Quandong Lian; Jianghong Yan; Shen Qu (Mine Water and the Environment, 2026)

Transcriptomics analyses reveal microgravity triggers estrogen synthesis amidst degeneration and aging in human ovarian granulosa cells - Changjian Yin; Jiaming Zhang; Zihang Cheng; Fang He; Haiquan Lu; Shigang Zhao (Life Sciences in Space Research, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Corrigendum to “Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data” [Int. J. Coal Geol. 320 (2026) 104999] - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Structured wave-transparent metamaterials for simultaneous broadband electromagnetic and acoustic absorption - Tongtong Zhang; Qingxuan Liang; Yubing Duan; Xin Yan; Aoqi Ren; Jiaming Feng; Dichen Li (Chemical Engineering Journal, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Development of an indirect ELISA and an immunochromatographic test method for early detection of Haemonchus contortus infection in sheep - Xueqiu Chen; Lingyun Mou; Manqin Deng; Jingju Zhang; Jiaming Yu; Jianfang Li; Hongli Zhang; Guangxu Ma; Yi Yang; Aifang Du (Veterinary Parasitology, 2026)

High turbidity induced by extreme precipitation complicates the relationships between molecular and optical properties of DOM in the Yangtze River - Yue Ren; Guangrui Yang; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (Journal of Water Process Engineering, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Structural properties of two glycans in the fruits of jujube and their regulation effect of M1-type and M2-type macrophage - Jingya Ruan; Ping Zhang; Jiaming Cheng; Lequan Yu; Yijin Wu; Yinuo Zheng; Yi Zhang; Tao Wang (Carbohydrate Polymers, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Impact of Sedimentary Environmental Evolution on Organic Matter Enrichment in Upper Paleozoic Marine-Continental Transitional Shales in the Shenfu Block, Eastern Ordos Basin, China: Evidence from Geochemistry - Yanchao Zhang; Xiangdong Yin; Shu Jiang; Litao Ma; Jiaming Li (Journal of Earth Science, 2026)

Influence of interface flow field on slope deterioration mechanism under freeze–thaw cycles: insights from physical model testing - Jiaming Zhang; Hao Xu; Xingyu Gao; Teng Liang; Xuecheng Bian (Transportation Geotechnics, 2026)

Transport modeling of ZVI-AC mixtures in Cr(VI) remediation driven by spectral induced polarization - Xinmin Ma; Alexis Maineult; Jiaming Zhang; Chen Chao; Ruijue Zhao; Jian Meng; Yaxun Wang; Deqiang Mao (Journal of Hazardous Materials, 2026)

Proof-of-concept evaluation of a 3D laser profiling system prototype for real-time woody breast detection of broiler breast fillets - Jiaming Zhang; Yuzhen Lu (Journal of Food Engineering, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Uniaxial compressive behavior of frozen silty clay at extreme low temperature with varying initial water content - Jiaming Xian; Wansheng Pei; Yuanming Lai; Mingyi Zhang; Fan Yu; Yanyan Chen (Cold Regions Science and Technology, 2026)

Adaptive Classification Model Based on Dynamic Variations in Microseismic Signal Characteristics - Jinglan Zhang; Jiaming Li; Beichang Tang; Shuguang Zhang; Shibin Tang (Rock Mechanics and Rock Engineering, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.

Prediction of Heterogeneous Shale Lithology in the Kaijiang–Liangping Trough Based on Dream Optimization Algorithm and Support Vector Machine - Lexin Yuan; Zhiming Xu; Haofei Sun; Jungang Lu; Luchuan Zhang; Xiangdong Yin; Jiaming Li (Mathematical Geosciences, 2026)

Sustainable development pathways of resource-based cities: the case of Xuzhou, China - Jiaming Zhang; Yunzhu Gui; Peiming He; Qingyun Tang (Environment, Development and Sustainability, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Anti-inflammatory metabolites from the leaves of Ohwia caudata - Qianqian Zhang; Ping Zhang; Yijin Wu; Huimin Li; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Synergistic layer engineering for high-efficiency blue emission in pure-bromide quasi-2D perovskite light-emitting diodes - Jiaming Yu; Bochao Jia; Shuguang Zhang; Yachun Guo; Yue Liang; Jiangshan Chen; Linfeng Lan; Junbiao Peng (Chemical Engineering Journal, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

Pipeline Systems in Floating Offshore Production Systems: Hydrodynamics, Corrosion, Design and Maintenance - Jin Yan; Yining Zhang; Zehan Chen; Pengji Li; Yuting Li; Zeyu Cao; Jiaming Wu; Kefan Yang; Dapeng Zhang (Journal of Marine Science and Engineering, 2026)
Floating offshore production systems play a critical role in offshore resource development, where the structural integrity and operational safety of risers, umbilical cables, and mooring cables are of paramount importance. Focusing on the failure risks of these key components under harsh marine environments, this paper systematically reviews the coupled mechanisms of wave-induced loading, electrochemical corrosion, and material fatigue. Unlike traditional reviews on offshore pipelines and cables, this study not only examines the mechanical performance of deepwater pipelines and cables along with representative research cases but also discusses corrosion mechanisms in marine environments and corresponding repair and mitigation strategies. In addition, recent advances in machine learning-based digital twin frameworks and real-time monitoring technologies are reviewed, with an analysis of representative application cases. The findings indicate that interdisciplinary material innovations combined with data-driven predictive models are essential for addressing maintenance challenges under extreme ocean conditions. Furthermore, this review identifies existing research gaps in data fusion for monitoring technologies and outlines clear directions for the intelligent operation and maintenance of future deep-sea infrastructure.

Fixed-time distributed adaptive neural network hybrid optimal output-feedback formation control for multi-USV systems - Jiaming Zhang; Wenjun Zhang; Shaocheng Tong (Ocean Engineering, 2026)

Monitoring contaminant removal during in situ chemical oxidation using cross-borehole resistivity tomography and hydrogeology - Teng Xia; Jiaming Zhang; Ruijue Zhao; Miao Li; Shupeng Li; Lili Guo; Deqiang Mao (Journal of Hydrology, 2026)

Changes in photo-reactivity and optical properties of dissolved organic matter during the freezing process of water - Man Yang; Jiaming Chen; Meng Yuan; Shuang Xue; Zhaohong Zhang (Journal of Environmental Management, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

A bead-based dendritic amplification system for multiplex miRNA detection - Feiyang Qian; Rui Zhu; Yao Lu; Tenghua Zhang; Yuqing Zhu; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

An Investigation of PSO-Optimized LSTM–Transformer Hybrid Model for Multi-Step Ship Motion Prediction - Yilu Peng; Qing Hai; Jiaming Zhang; Lingwei He; Yongyu Huang; Lin Du; Yiming Qiang (Journal of Marine Science and Engineering, 2025)
The advantages of hybrid models for time series forecasting have received significant attention, and several studies focus on and test their application in the seakeeping of ship motions. A hybrid model integrating an LSTM encoder and Transformer decoder (LT) is introduced to overcome the limitation of individual LSTM and Transformer: initially, the seakeeping response of the KCS ship was simulated by ANSYS-AQWA considering the sea state 3 and 4 simultaneously and established a dataset; secondly, three standalone baseline models (LSTM, Transformer, and TCN), and two hybrid models, LT and LT, with PSO-optimized hyperparameters (P-LT) were constructed and trained to forecast the seakeeping performance of ships with multiple steps of 30, 60 and 90; finally, the comparison between solo and hybrid models was made by different steps on RMSE, MAE and NRMSE evaluations to prove the advancement of LT and P-LT models. The P-LT hybrid model achieved consistent accuracy improvements compared with the best-performing individual models across different ship motions. Notably, RMSE reductions were observed at all prediction horizons (30, 60, and 90 steps), with maximum improvements reaching 13.54% for rolling, 11.83% for pitching, and 12.87% for heaving motions. This study provides both theoretical and practical support to ship motion prediction and demonstrates the potential of the proposed study as an effective engineering product for enhancing safety in ship operation.

Spatial-interaction-context and temporal-attention U-Net model for spatio-temporal prediction of Sea Surface Temperature field - Jiaming Ma; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai; Yuan Zhang; Jie Tian; Ming Li (Regional Studies in Marine Science, 2025)

Synergizing machine learning and interpolation methods: A Stacking framework for global-scale satellite soil moisture gap filling - Jiaming Rong; Jiangyuan Zeng; Kun-Shan Chen; Hongliang Ma; Pengfei Shi; Husi Letu; Xiang Zhang; Xihui Gu; Haiyun Bi; Chunlin Zhang (Remote Sensing of Environment, 2025)

Potential strategies of natural products in the treatment of atherosclerosis: Focusing on modulating macrophage polarization - Wenjie Zhao; Peng Sun; Jiaming Huan; Lei Zhang; Shijing Peng; Tong Jiang; Linghui Kong; Xinghao Zhu; Wenqing Yang; Dongmei Qi; Yunlun Li (PharmaNutrition, 2025)

Thermophilic antagonistic/competitive networks drive low nitrogen loss in Phase I commercial composting: Deciphering microbe-nitrogen coupling using the novel multistep interaction validation analysis - Yu Sun; Jiaming Fan; Yue Zhang; Zhaoxue Gai; Shuai Shi; Xiuhong Xu (Journal of Environmental Chemical Engineering, 2025)

Reshaping spatial–temporal pattern of suspended sediment concentration in the Yangtze River mainstem by damming reservoirs based on nearly 40 years Landsat observations - Farong Chen; Guangrui Yang; Yanhui Dai; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Porcine liver peptide ameliorates ethanol-induced liver injury via the NQO1 and ACAA1 signaling pathway through regulating oxidative stress and lipid metabolism - Zixu Wang; Lujuan Xing; Jingyu Wang; Jiaming Cai; Yuejing Hao; Ye Tao; Wangang Zhang (Food Bioscience, 2025)

CRISPR/Cas12b-mediated one-tube live cell assay facilitates Salmonella typhimurium detection in poultry meat - Yongjin Dai; Jiaming Huang; Moran Zhang; Xinyi Pang; Xiangfei Li; Jing Sun; Yingjian Lu (Food Bioscience, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

A differentiated study of the impact of command and market-based environmental regulation on corporate R&D investments —take China's coal power industry chain as an example - Jiaming Gao; Li Zhang (Energy Policy, 2025)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Thermostatic nucleic acid amplification technology in foodborne pathogen detection: opportunities and challenges - Moran Zhang; Jiaming Huang; Yongjin Dai; Shanshan Jin; Qianqian Jia; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (Critical Reviews in Food Science and Nutrition, 2025)

A Novel Approach for Fast Microplastic Quantification in Sediments Using Machine Learning—Spectrometer Combinations - Piao Yao; Jiaming Zhang; Bin Zhou; Yang Chen; Ding He (Water, Air, & Soil Pollution, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

How to restrict informal recycling of photovoltaic modules: Research on closed-loop supply chain decision-making of photovoltaic modules under different recycling subsidy policies - Jiaming Gao; Li Zhang (Journal of Cleaner Production, 2025)

Response of bacterial pathogens to process upgrades and floc sizes in a full-scale landfill leachate treatment plant - Binbin Sheng; Shitong Liu; Kenan Xiong; Jiaming Liu; Shuang Zhu; Haipeng Zhang; Rongxin Zhang (Journal of Environmental Management, 2025)

Energy analysis and microfracture characteristics of granite under dynamic modes I and II loading based on image processing techniques - Zida Liu; Zong-Xian Zhang; Quanqi Zhu; Peng Xiao; Jiaming Yang; Diyuan Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Adaptive isoline interval optimization for precise contour segmentation and instance-level detection of Martian impact craters - Dong Chen; Fan Hu; Jiaming Na; Zhenxin Zhang; Zhen Cao; Liqiang Zhang; Zhizhong Kang; Jiju Poovvancheri; Norbert Pfeifer (Icarus, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

ZnP-H2Im glass for flame retardant wood: In situ vitrification and synergistic mechanisms - Zhipeng Zhang; Jinrong He; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

Hybrid fabrication of perfusable stiffness-flexible integrated scaffold mimicking hierarchical tubular bone - Yifan Zhang; Zhipeng Li; Bingkun Bao; Jingyi Ju; Wenbin Jiang; Linyong Zhu; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

An in-situ generated multiphase catalyst for active and durable ammonia protonic ceramic fuel cells - Haiyang Lan; Zixuan Xue; Jiakun Sun; Jiaming Chu; Jiangyuan Feng; Weitao Jin; Zixian Wang; Ruiqing Song; Pengfei Yan; Liang Zhang; Yucun Zhou; Xiaofeng Ye; et al. (Chemical Engineering Journal, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Floodplain hydrodynamics and connectivity in a natural compound channel during unsteady flow events - Jiaming Liu; Yang Xiao; Saiyu Yuan; Taotao Zhang; Qingwei Lin; Kang Yuan; Ruiqi Wang; Carlo Gualtieri (Journal of Hydrology, 2025)

Investigation of nTiO2-WTe2 (n = 1–3) nanocluster sensors for the detection of toxic gases H2S, NH3, and NO2 in agricultural greenhouses: A DFT study - Haoming Zhang; Jiaming Jiang; Wen Zhou; Qu Zhou (Journal of Environmental Chemical Engineering, 2025)

Impact of dynamic desiccation cracks on hydrological processes and stability in expansive clay slopes: A coupled dual-permeability modeling approach - Yi Luo; Jiaming Zhang; Chao-Sheng Tang; Guosheng Jiang; Thom Bogaard (Engineering Geology, 2025)

Br− as a potential suppressor of NDMA formation during ozonation of HDMS: Mechanisms and implications - Fan Zhou; Menglan Gao; Xiaobin Liao; Jiaming Zhu; Zhenkun Chen; Huatong Ma; Huayu Zhang; Jin Wang; Chenyang Liao; Mingzhi Huang; Zhimin Yang (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Hydrodynamic Optimization and Motion Stability Enhancement of Underwater Glider Combining CFD and MOPSO - Tian Zhang; Jiaming Wu; Xianyuan Yang; Xiaodong Chen (Journal of Marine Science and Engineering, 2025)
This study investigated the motion stability of underwater gliders and optimized their shape to enhance hydrodynamic performance. Given the critical role of stability in underwater operations, a multi-objective optimization framework was developed, focusing on the geometric configuration of hydrofoils. Computational fluid dynamics (CFD) simulations were employed, with stability assessed based on hydrodynamic moments in roll and pitch motions. A surrogate model was constructed using Kriging interpolation, leveraging Latin hypercube sampling (LHS) to generate 60 design points. Sensitivity analysis identified key shape parameters influencing stability, guiding a multi-objective particle swarm optimization (MOPSO) algorithm to explore optimal design configurations. Improvements of up to 68.91% in roll stability and 51.63% in pitch stability are achieved compared to the original model, which demonstrates the effectiveness of the proposed optimization approach. The findings provide valuable insights into the hydrodynamic design of underwater gliders, facilitating enhanced maneuverability and stability in complex marine environments.

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Construction of biochar-zeolite composite for enhanced VOCs adsorption: Interfacial reinforcement and steam-driven synergistic regulation of pore formation and dealumination - Dingcheng Liang; Yajie Chang; Peipei Zhang; Yuan Liu; Chenhong Luo; Zhijun Zhang; Qiang Xie; Jiaming Liang; Kangzhou Wang; Xiao Yang; Qingping Chen; Zhucan Xie; et al. (Journal of Cleaner Production, 2025)

Investigation on hydraulic conductivity reduction for silty sand by enzyme induced calcium carbonate precipitation considering urease activity and cementing solution concentration - Lei Shi; Liuhui Huo; Jiaming Fang; Xiangchun Xu; Jianwei Zhang (Engineering Geology, 2025)

Towards efficient in situ gas thermal desorption remediation assisted with cross-borehole resistivity tomography - Teng Xia; Jiaming Zhang; Miao Li; Shupeng Li; Lili Guo; Peng Liu; Dixiang Wang; Deqiang Mao (Water Research, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

Highly selective aerobic oxidation of polystyrene to benzoic acid catalyzed by nitrogen dioxide - Yunkai Yu; Yue Zhu; Jiaming Liu; Minghao Zhang; Jing Li; Shicheng Zhang; Qingqing Mei (Science Bulletin, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Dynamic optimization of cooling temperature setpoints in multiple thermal zones of office buildings in connection with D3QN - Ben Jiang; Jiaming Wang; Yu Li; Peng Wang; Yacine Rezgui; Chengyu Zhang; Menglin Ding; Liuyang Shangguan; Tianyi Zhao (Energy and Buildings, 2025)

Extraction of Chlorella polysaccharide using natural deep eutectic solvent - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Huiqing Zhang; Changhua Shang (Algal Research, 2025)

Purification and characterization of cellulase produced by Bacillus sp. HMM - Lanqian Huang; Lei Mo; Jiaming Jiang; Yu Huo; Shisong Yu; Jianmei Ou; Siyu Liu; Xinyu Xie; Guyu Yan; Chuzun Liao; Shangxin Wu; Huiqing Zhang; et al. (Antonie van Leeuwenhoek, 2025)

Better inversion of rice nitrogen nutrition index at early panicle initiation stage using spectral features, texture features, and wavelet features based on UAV multispectral imagery - Ziwei Li; Yuliang Zhang; Jiaming Lu; Yuan Wang; Can Zhao; Weiling Wang; Jianjun Wang; Hongcheng Zhang; Zhongyang Huo (European Journal of Agronomy, 2025)

Insight of multi-polarization effect by constructing high-entropy spinel ferrite/perovskite @ amorphous carbon for enhancing electromagnetic wave absorption - Xinyang Liu; Zhekai Zhang; Fengyu Wu; Fenyang Tian; Jie Sheng; Menggang Li; Jiaming Li; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2025)

3D printing programmed diagnostic and therapeutic bioactive “all-in-one” microspheres with multistimuli responsiveness for cartilage regeneration - Feifei Zhou; Wenjing Zhang; Yuan Yang; Shuyu Liu; Jing Long; Siqi Zhang; Jiaming Cui; Yuxiao Lai; Weimin Zhu (Chemical Engineering Journal, 2025)

Task-Sequencing Optimization Using DSSA Algorithm for AUV with Limited Endurance - Qixin Sha; Jiaming Zhang; Yue Shen; Bo He (Journal of Marine Science and Engineering, 2025)
Efficiency is very important for robots when executing multiple tasks, especially for autonomous underwater vehicles (AUVs) with limited endurance. In order to improve efficiency, task-sequencing optimization, which focuses on achieving the optimal execution order of multiple tasks, is one effective way. In this paper, the classic lawnmower traverse task is taken as an example for optimization, and discrete salp swarm algorithm (DSSA), which combines salp swarm algorithm (SSA) and genetic algorithm (GA), is selected and applied to optimize task sequencing for one AUV. In the optimization process, there are two key problems that need to be solved. One is how to encode the individual chromosome and the other is how to perform genetic operations on chromosomes of different lengths. For the former problem, a two-layer encoding method is proposed to generate individuals in the population, in which identity number and entry point of different areas are encoded, respectively. For the latter problem, mutation and crossover operators are modified and extended to deal with individuals of variable length due to the limited endurance of AUVs. Simulation results show that the sequencing optimization can be achieved after finite iteration. Through comprehensive comparison, DSSA is finally implemented and verified in a physical AUV.

Efficient and anti-interference plastic classification method suitable for one-shot learning based on laser induced breakdown spectroscopy - Zhiying Xu; Xingyu Zhao; Xinying Peng; Kai Wang; Kedong Wang; Nan Zhao; Jiaming Li; Qingmao Zhang; Xueqing Yan; Kun Zhu (Chemosphere, 2025)

Study on rockburst control of deep-buried tunnel by combining advanced stress release borehole and hydraulic fracturing - Jiaming Li; Shibin Tang; Tianjiao Li; Shuguang Zhang; Liexian Tang; Kang Sun (Tunnelling and Underground Space Technology, 2025)

Global-scale gap filling of satellite soil moisture products: Methods and validation - Chunlin Zhang; Jiangyuan Zeng; Pengfei Shi; Hongliang Ma; Husi Letu; Xiang Zhang; Panshan Wang; Haiyun Bi; Jiaming Rong (Journal of Hydrology, 2025)

GACraterNet: A collaborative geometry-attribute domain network for enhanced detection of Martian impact craters - Fan Hu; Dong Chen; Jiaming Na; Zhen Cao; Zhenxin Zhang; Liqiang Zhang; Zhizhong Kang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Ultrasensitive nanoenzymes-based lateral flow immunoassay platform for accurate detection of folic acid in human serum - Jinbo Cao; Tiemei Li; Xianglin Liao; Jiaming Zhang; Xixiang Yang; Huiqi Yan; Boyang Sun; Yanfei Li; Jiaxiang Huang; Yao Wang; Xiaogang Hu; Li Wang (Chemical Engineering Journal, 2025)

Enhancing cancer-killing activity of PMN transfusion therapy via apoptotic modulation function of selenium nanoparticles - Chenyu Lin; Jing Wang; Yuqian Zhu; Dachuan Zhang; Xixi Huang; Jiaming Wang; Jianlin Ren; Ming Hou; Mufan Wu; Bing Shen; Bingdi Chen (Chemical Engineering Journal, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Multitask intelligent early warning of rockbursts based on classification-regression cascaded network model - Jiaming Li; Shibin Tang; Jinglan Zhang; Beichang Tang; Shuguang Zhang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Catalytic ozonation of sulfamethoxazole using loaded CuOx/MgO-SiO2 silica aerogel catalyst: Performance, mechanisms and toxicity - Lanhe Zhang; Jiaming Wu; Jian Zhang; Jingbo Guo (Environmental Research, 2025)

Highly stable anode-free solid-state sodium batteries enabled by electrostatic shielding and nitrogenated interphase - Wuliang Feng; Caixia Li; Peiyao Wang; Jiaming Hu; Xuan Yu; Ying Zhang; Xingbao Zhu; Dengsong Zhang; Yongyao Xia; Yufeng Zhao (Chemical Engineering Journal, 2025)

Engineering cuttlefish melanin nanoparticles: A dual-action therapy for acute radiation syndrome and combined radiation-wound injuries via regulating Bcl-2 family proteins and caspases in the apoptotic process - Zhemeng Zhao; Bin Hu; Danfeng Zhang; Xinyue Cui; Wen Ding; Tongshuai Wang; Jingyi Wang; Ziyi Guo; Yingtang Zhou; Shige Wang; Jiaming Guo (Chemical Engineering Journal, 2025)

Low-dose exposure to microplastics retards meiotic maturation via HDAC3 insufficiency - Qi Zhao; Ming Zong; Entong Song; Hongye Linghu; Xuanwen Li; Baicui Wang; Songling Xiao; Wanchun Guan; Jianzhong Su; Jiaming Zhang; Jingzhang Ji; Qingran Kong (Science China Life Sciences, 2025)

ADAM17 promotes colorectal cancer migration and invasion by regulating the TGF-β/Smad signaling pathway - Jiaming Li; Tingjin Zheng; Yingzhi Xu; Mengcha Tian; Liangpan Shi; Jintu Chen; Tian Li; Zhishan Zhang (Tissue and Cell, 2025)

Ternary Fenton-like material (γ-Fe2O3/MoS2/PANI) supported on polysulfate membrane for high-performance catalytic degradation of tetracycline solution - Jiaming Xu; Heng Zhang; Lian-Biao Zhao; Xiaohong Xing; Junlan Tang; Xiangru Zhou; Lincheng Zhou (Journal of Water Process Engineering, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

Multi-omics revealed activation of TNF-α induced apoptosis signaling pathway in testis of DEHP treated prepubertal male rat - Zishui Fang; Zirun Jin; Qiancheng Zhao; Jiaming Weng; Zhe Zhang; Yuzhuo Yang; Hui Jiang (Reproductive Toxicology, 2025)

Interaction between imidacloprid residues in maize rhizospheric soil and soil nematode community - Jiaming Zhang; Yue Wu; Jiayi Liu; Xinru Wang; Weijia Pang; Juan Hua; Shihong Luo (Pesticide Biochemistry and Physiology, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Rheological and thermal property of KH570-modified nano-SiO2 grafted xanthan gum and its application in drilling fluid system - Jingqi Shi; Long Chen; Ruihan Xie; Jiayin Zhang; Shuangcheng Pi; Jiaming Yang; Yunhai Zhao; Feng Xiong; Yongkui Zhang; Tonghui Xie (Carbohydrate Polymers, 2025)

Evolution of in-situ thermal-enhanced oxidative remediation monitored by induced polarization tomography - Teng Xia; Jiaming Zhang; Miao Li; Damien Jougnot; Kai Yang; Shupeng Li; Deqiang Mao (Journal of Hydrology, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

A functional fluorine (F)-containing oxidiser of nano-networked NH4CuF3 to improve the combustion efficiency of Al powder - Xiandie Zhang; Haozhe Li; Xuxu Cui; Weiduo Fei; Xinwen Ma; Jiaming Liu; Pingyun Li; Xiaode Guo; Xiang Zhou (Fuel, 2025)

Overcoming carbon deposition in non-thermal plasma catalyzed biomass tar reforming: Innovative strategies employed by GPPC systems - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Yiqiang Liu; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Guilin Piao (Fuel, 2025)

Fabrication and saltiness enhancement of salt hollow particles by interface migration - Kailin Ye; Jiafeng Chen; Xinyu Zhang; Jiaming Qi; Zihan Qin; Jinmei Wang (Food Research International, 2025)

Tracking Cr(VI) removal with spectral induced polarization under ZVI and AC synergetic remediation - Xinmin Ma; Jiaming Zhang; Chen Chao; Shiliang Liu; Khalil Ur Rahman; Shupeng Li; Lili Guo; Deqiang Mao (Environmental Research, 2025)

High performance two photon polymerization resin designed for sub-micron precision and millimeter scale structure manufacturing - Jiaming Hu; Yang Gao; Lukun Wu; Bowen Zheng; Ning Li; Kai Du; Jing Li; Shuai Zhang (Chemical Engineering Journal, 2025)

Efficient Removal of Cr(VI) by Bamboo-Derived Biochar Supported Nano Zero-Valent Iron: Insights into Performance and Mechanism - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Yunlong Zhu; Jianbing Lu; Yang Gao; Mingjuan Zhang; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Safety control of blasting vibration in new tunnel excavation adjacent to existing tunnel - Junru Zhang; Zhijian Yan; Jianchi Ma; Qihua Deng; Jiaming Liu; Jimeng Feng; Zhiyong Wang (Bulletin of Engineering Geology and the Environment, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Fish Community Diversity and Spatiotemporal Dynamics in the Downstream of the Fujiang River Based on Environmental DNA - Jiaming Zhang; Yifang Chen; Xinxin Zhou; Jiaxin Huang; Xiaohan Dong; Shuli Zhu; Yanjun Shen (Fishes, 2025)
Hydrological changes caused by dam construction are among the primary drivers of global freshwater biodiversity decline. To assess the current status of fish community diversity and examine the impacts of cascade hydropower development on fish diversity, this study employed environmental DNA (eDNA) technology from 2023 to 2024 to conduct seasonal surveys at 18 sampling sites across six river segments separated by five dams in the downstream section of the Fujiang River. The study aimed to uncover the temporal and spatial dynamics of fish diversity and community structure, as well as to analyze the influence of environmental factors on these patterns. The results identified 84 fish species spanning 60 genera, 19 families, and 7 orders, including 2 nationally protected species, 11 endemic species of the upper Yangtze River, and 13 alien species. The cascade dams were found to have significantly reduced fish diversity compared to historical records, with a marked decline in native species and a rise in alien species, contributing to the miniaturization and homogenization of fish communities. Environmental factor analysis revealed that chemical oxygen demand (COD), dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity (EC), and reservoir formation time were significant drivers of fish community structure and diversity. This study provides essential baseline data on fish diversity under the influence of cascade hydropower development in the Fujiang River. It also offers valuable insights into the current status of fish resources and supports efforts in fish conservation and aquatic ecosystem management in the region.

Cell wall and reactive oxygen metabolism responses of stored Shine Muscat grapes to combined melatonin and 24-epibrassinolide treatment - Yaoying Zeng; Jiaming Zhang; Hui Su; Le Xie; Ye Zhao; Yubo Xiong; Zhou Wenhua (Postharvest Biology and Technology, 2025)

Adaptive fuzzy optimal output-feedback fault-tolerant control for the USV system with intermittent actuator faults - Jiaming Zhang; Wenjun Zhang; C.L. Philip Chen; Shaocheng Tong (Ocean Engineering, 2025)

Enhanced steam reforming of benzene in a two-stage catalytic system: Insights into metal synergies and carbon deposition evolution - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Yuan Sun (Fuel, 2025)

Insights into the combustion mechanisms of turpentine oil based on ReaxFF molecular dynamics simulations - Chongchong She; Tiancheng Zhang; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Haversian bone mimicking scaffold with built-in vasculature for bone tissue engineering - Jian Liu; Zhen You; Xinmei Li; Boyang Zhang; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Mapping QTLs for stigma exsertion-related traits in two sets of CSSL populations of Oryza sativa cultivars using RSTEP-LRT method - Chunyu Jing; Mei Hai; Jiaming Shen; Xinru Li; Mengyuan Zhang; Changmin Hu; Qing Xu; Jianhua Jiang; Xiaojing Dang (Euphytica, 2025)

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Soil infiltration mechanisms under plant root disturbance in arid and semi-arid grasslands and the response of solute transport in rhizosphere soil - Yuanyuan Jia; Huan Huan; Wenjing Zhang; Bo Wan; Jiaming Sun; Zhipeng Tu (Science of The Total Environment, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

Numerical simulation of aerated flow in tunnel based on CFD-PBM coupled model - Jiaming Lei; Jianmin Zhang (Ocean Engineering, 2024)

Can wood harvest followed by forest regrowth enhance carbon sequestration of the forest sector in China? - Mengyu Wang; Chao Yue; Junhao He; Pengyi Zhang; Mengyang Xu; Yu Li; Jiaming Wang; Lele Wang; Can Xu (Global and Planetary Change, 2024)

Study on strength and reduction characteristics of iron ore powder-green carbon composite briquettes - Yifan Chai; Shijie Wang; Jiaming Zhang; Yanshuo Shi; Peijun Liu; Shengli An; Chuan Wang; Xiaojun Ning (Fuel, 2024)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

Microbial community dynamics in different floc size aggregates during nitrogen removal process upgrading in a full-scale landfill leachate treatment plant - Binbin Sheng; Shitong Liu; Kenan Xiong; Jiaming Liu; Shuang Zhu; Rongxin Zhang (Bioresource Technology, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Whole genome sequencing and analysis of Bacillus sp. TTMP2, a tetramethylpyrazine-producing bacterium - Shanling Gan; Lingru Ruan; Xinyi Xu; Lirong Luo; Yu Huo; Jiaming Jiang; Xiumin Zhang; Changhua Shang (Molecular Biology Reports, 2024)

Spatial Patterns and Drivers of Intelligent Manufacturing from a ‘Global-local’ Perspective: A Study of China’s Industrial Robotics - Fengjiao Li; Hong Zhang; Lili Jiang; Jiaming Liu (Chinese Geographical Science, 2024)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

Near-infrared responsive photocatalysts for environmental remediation and energy conversion: A review - Jiaming Li; Yuan Li; Dmitry Selishchev; Gaoke Zhang (Chemosphere, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Quasi-homogeneous photoelectrochemical organic transformations for tunable products and 100% conversion ratio - Cheng Lin; Yuan Lu; Jiaming Miao; Zhongyuan Ma; Youngmoon Choi; Yan Yang; Chaoran Dong; Jinyou Shen; Jong Hyeok Park; Kan Zhang (Science Bulletin, 2024)

Adaptive neural optimal tracking control for uncertain unmanned surface vehicle - Jiaming Zhang; Wenjun Zhang; Shaocheng Tong (Ocean Engineering, 2024)

Water-induced surface ordering facilitating the microcutting of ductile metals - Jiong Zhang; Xiaopeng Wang; Lu Ma; Shibo Xi; Jiaming Zhan; Ruipeng Li; Yonghua Du; Junmin Xue; Hao Wang (Journal of Cleaner Production, 2024)

Co-governance of open pit mines across China based on exposure risk assessment of particulate matter - Shuo Lu; Wenzhong Zhang; Peng Zeng; Jiaming Li (Journal of Cleaner Production, 2024)

Construction of La1−xSrxNiO3/g-C3N4 type-Z heterojunctions with enhanced visible-light photocatalytic degradation of organic pollutants - Pengke Yu; Jiaxing Guo; Liang Guo; Yaqin Deng; Juntao Tan; Qunang Xu; Qingmao Zhang; Jiaming Li (Environmental Research, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Enhanced photocatalytic CO2 reduction to CH4 on oxygen vacancy-rich NiCo2O4 with surface pits: Synthesis, DFT calculations, and mechanistic insights - Jiaming Li; Yuan Li; Minsu Han; Yusuke Yamauchi; Gaoke Zhang (Chemical Engineering Journal, 2024)

Building block design of thermally regenerable metal–organic framework composites for highly selective lithium adsorption - Xinyu Zhang; Xu Wu; Jiaming Gan; Xin Yu; Huanting Wang; Ranwen Ou (Chemical Engineering Journal, 2024)

Regulatory mechanisms of miR171d–SCL6 module in the rooting process of Acer rubrum L. - Huiju Li; Jiayu Yu; Jiaming Qin; Hewen Zhao; Kezhong Zhang; Wei Ge (Planta, 2024)

Unmanned Surface Vessel–Unmanned Aerial Vehicle Cooperative Path Following Based on a Predictive Line of Sight Guidance Law - Hugan Zhang; Jiaming Fan; Xianku Zhang; Haitong Xu; C. Guedes Soares (Journal of Marine Science and Engineering, 2024)
This paper explores the cooperative control of unmanned surface vessels (USVs) and unmanned aerial vehicles (UAVs) in maritime rescue and coastal surveillance. The USV-UAV system faces challenges of disturbances and substantial inertia-induced overshooting during path following. A novel position prediction line of sight (LOS) guidance law is proposed to address these issues for USV path following control. Radial basis function-based neural networks (RBF-NNs) are used to estimate disturbances, and a high-order differentiator is used to design a velocity observer for unknown USV velocity. The UAV control system employs proportional–derivative (PD) control with feedforward compensation for quadrotor control design and utilizes a finite-time converging third-order differentiator to differentiate non-continuous functions. The simulation results demonstrate strong robustness in the proposed USV-UAV cooperative control algorithm. It achieves path following control in the presence of wind and wave disturbances and exhibits minimal overshoot.

Innovative approach to enhancing phosphogypsum mechanical properties and stabilizing/solidifying contaminants - Lina Xiao; Jiaming Zhang; Yi Luo; Xiaojian Qi; Javid Hussain; Guosheng Jiang (Sustainable Chemistry and Pharmacy, 2024)

Transport processes of dissolved and particulate nitrogen and phosphorus over urban road surface during rainfall runoff - Yang Xiao; Chi Zhang; Taotao Zhang; Bin Luan; Jiaming Liu; Qiang Zhou; Chentao Li; Haoke Cheng (Science of The Total Environment, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

ILP1 and NTR1 affect the stability of U6 snRNA during spliceosome complex disassembly in Arabidopsis - Jiaming Wu; Wei Chen; Shengchao Ge; Xueliang Liu; Junling Shan; Meishan Zhang; Yuan Su; Yunfeng Liu (Plant Science, 2024)

Online sorting of surface defective walnuts based on deep learning - Jingwei Wang; Xiaopeng Bai; Daochun Xu; Wenbin Li; Siyuan Tong; Jiaming Zhang (Journal of Food Engineering, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Optimal classification of radiant time series for cooling load calculation of building air-conditioning systems - Jing Ren; Youming Chen; Xinchao Zhang; Jiaming Liu (Energy and Buildings, 2024)

Significantly enhancing high-temperature piezoelectric response and Tdr of BF-BT-based ceramics through multi-component optimization strategy - Huabin Yang; Jiaming Zhu; Xueting Wang; Qiuling Luo; Hua Tan; Haibo Zhang; Jiwen Xu; Qiaohong Chen (Chemical Engineering Journal, 2024)

Effects of dry-wet cycles on the mechanical properties of sandstone with unloading-induced damage - Gan Nan; Jiaming Zhang; Yi Luo; Xinlong Wang; Zhongyi Hu (Journal of Mountain Science, 2024)

Numerical research on the influence of ocean conditions on the transient response of passive decay heat removal system of the floating Fluoride-Salt-Cooled High-Temperature Reactors - Limin Liu; Ziyin Liu; Jiaming Zhang; Cong Shen; Maolong Liu; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

A novel intelligent indoor fire and combustibles detection method based on multi-channel transfer learning strategy with acoustic signals - Zhihua Wang; Zipeng Zhang; Zhuoyue Wang; Jiaming Lu; Weiguang An (Process Safety and Environmental Protection, 2024)

Mechanism and toxicity assessment of Cu0/Fe3O4 activated persulfate based on the acceleration cycle of Fe3+/Fe2+ for the degradation of methyl orange - Lanhe Zhang; Qi Zhang; Chuan Xiao; Yanping Jia; Jiaming Wu (Journal of Water Process Engineering, 2024)

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

Assessing geological hazard susceptibility and impacts of climate factors in the eastern Himalayan syntaxis region - Jiaming Yao; Yanbing Wang; Teng Wang; Beibei Zhang; Yuming Wu; Xin Yao; Zheng Zhao; Shu Zhu (Landslides, 2024)

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Kinematic Stability Analysis of Anchor Cable Structures in Submerged Floating Tunnel under Combined Parametric–Vortex Excitation - Jiaming Xiong; Song Sang; Youwei Du; Chaojie Gan; Ao Zhang; Fugang Liu (Journal of Marine Science and Engineering, 2024)
The submerged floating tunnel is a marine transportation infrastructure that links two shorelines. The tunnel tube body’s buoyancy exceeds gravity, with anchoring ensuring equilibrium. Anchoring reliability is crucial. This study presents a three-way coupled kinematic model for the mooring structure, formulated on Hamilton’s principle and Kirchhoff’s assumption. It explores the impact of the tube body’s buoyancy-to-weight ratio and the sea current’s angle of incidence on mooring motion response. By solving the motion analysis model, Hill’s equation system is derived to assess the parameter instability of the anchor cable structure. The coefficient of excitation instability intervals for the submerged floating tunnel is determined and validated. The findings indicate the following: (1) Increasing the float-weight ratio reduces displacement response amplitudes in all directions, bringing downstream and transverse currents closer to their initial positions; (2) Changes in current direction angles result in decreased downstream excitation strength and increased transverse displacement response with the same excitation direction; (3) The instability interval visualization effectively predicts anchor cable structure instability under parametric excitation. Structures within the instability region are deemed unstable, while those outside are considered stable.

LSGNet: A lightweight convolutional neural network model for tomato disease identification - Shengxian Yang; Licai Zhang; Jianwu Lin; Tomislav Cernava; Jitong Cai; Renyong Pan; Jiaming Liu; Xingtian Wen; Xiaoyulong Chen; Xin Zhang (Crop Protection, 2024)

Facet-dependent activation of oxalic acid over hematite nanocrystals under the irradiation of visible light for efficient degradation of pollutants - Zhixiong Yang; Yuan Li; Xiaotian Wang; Jiaming Li; Jiquan Wang; Gaoke Zhang (Journal of Environmental Sciences, 2024)

Boosting charge transfer promotes photocatalytic peroxymonosulfate activation of S-doped CuBi2O4 nanorods for ciprofloxacin degradation: Key role of Ov–Cu–S and mechanism insight - Xianzhong Bu; Jiaming Li; Jin Wang; Yuan Li; Gaoke Zhang (Chemical Engineering Journal, 2024)

Hydrocarbon Source and Relationship between Hydrocarbon Charging Process and Reservoir Tight Period of the Denglouku Formation Tight Sandstone Gas Reservoirs in the Xujiaweizi Fault Depression, Songliao Basin - Huan Miao; Zhenxue Jiang; Jiaming Lu; Chengju Zhang; Lidong Shi; Lidong Sun; Liang Yang; Peng Shang (Natural Resources Research, 2024)

Effects of DeSUMOylated Spastin on AMPA Receptor Surface Delivery and Synaptic Function Are Enhanced by Phosphorylating at Ser210 - Wenbin Zhang; Jiaqi Zhang; Zhongqi Zhang; Shuhan Cha; Jiong Li; Li Chen; Jiaming Wu; Jijun Teng; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2024)

Genome-wide identification and expression analysis of the SOD gene family under biotic and abiotic stresses in sweet orange - Xulin Li; Ke Wen; Tuo Yin; Chaoying Chen; Ling Zhu; Xiuyao Yang; Yinqiang Zi; Ke Zhao; Jiaming Zhang; Hanyao Zhang (Plant Biotechnology Reports, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Joint optimal allocation of regional water and land resources considering their mutual feed relationship - Chengguo Su; Zhenglei Hu; Wenlin Yuan; Jiaming Zhang; Denghua Yan; Huiliang Wang (Journal of Hydrology, 2024)

Towards sustainable development in resource-based cities: Assessing the effects of extraregional technology and investment on the low-carbon transition - Shuo Lu; Jiaming Li; Wenzhong Zhang; Fan Xiao (Journal of Environmental Management, 2024)

Contributions of China's terrestrial ecosystem carbon uptakes to offsetting CO2 emissions under different scenarios over 2001–2060 - Mengyang Xu; Ziyu Zhang; Chao Yue; Jie Zhao; Pengyi Zhang; Mengyu Wang; Jiaming Wang; Hongfei Zhao; Jinyue Liu; Xianhui Tang; Junhao He (Global and Planetary Change, 2024)

Effects and mechanisms of ultrasound-assisted emulsification treatment on the curcumin delivery and digestive properties of myofibrillar protein-carboxymethyl cellulose complex emulsion gel - Lei Zhou; Jiaming Cai; Jingyu Wang; Chao Ma; Lujuan Xing; Siah Ying Tang; Wangang Zhang (Food Research International, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Identification of toll-like receptor family and the immune function of new Sptlr-6 gene of Scylla paramamosain - Bohao Peng; Jiaming Lin; Haifu Wan; Pengfei Zou; Ziping Zhang; Yilei Wang (Fish & Shellfish Immunology, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Applicability and limitation of compost maturity evaluation indicators: A review - Yilin Kong; Jing Zhang; Xuanshuo Zhang; Xia Gao; Jie Yin; Guoying Wang; Jiaming Li; Guoxue Li; Zhongliang Cui; Jing Yuan (Chemical Engineering Journal, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Synthesis and antiviral property of polysulfate-grafted maleimide-based enediynes - Zhuoyu Li; Zhe Ding; Haonan Cheng; Xiaofan Zhang; Houjun Zhang; Gary Wong; Yun Ding; Jiaming Lan; Aiguo Hu (Medicinal Chemistry Research, 2024)

Effects of improper emergency mitigations on a large-scale landslide triggered by road excavation: A case study of the Fengping landslide, Hubei province, China - Yi Luo; Jiaming Zhang; Zhi Zhou; Guosheng Jiang; Modong Duan (Bulletin of Engineering Geology and the Environment, 2024)

Live chicken body fat measurement technology based on bio-electrical impedance - Jiaming Zuo; Jinping Liang; Shangshang Cheng; Yuelin Deng; Zhenhui Li; Qinghua Nie; Dexiang Zhang; Xiquan Zhang; Zhen Li; Hongmei Li (Computers and Electronics in Agriculture, 2024)

Cooling and optimizing urban heat island based on a thermal knowledge-informed multi-type ant colony model - Zhaomin Tong; Jiaming Yang; Yaolin Liu; Ziyi Zhang; Sui Liu; Yanchi Lu; Bowen Pang; Rui An (Remote Sensing of Environment, 2024)

Mechanism study on the effect of heat shock on the functional characteristics of soybean protein isolate by regulating the change of endogenous enzyme activity in soybeans - Feng Yan; Shisheng Tong; Jiaming Zhang; Yuanyuan Zhao; Ping Liu (Food Hydrocolloids, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

Biochanin a ameliorates DSS-induced ulcerative colitis by improving colonic barrier function and protects against the development of spontaneous colitis in the Muc2 deficient mice - Haina Zhang; Xueqi Wang; Linxian Zhao; Kai Zhang; Jiaming Cui; Guangmeng Xu (Chemico-Biological Interactions, 2024)

Development of a 3D point cloud reconstruction-based apple canopy liquid sedimentation model - Chongchong Chen; Yalan Jia; Jiaming Zhang; Linsen Yang; Yaxiong Wang; Feng Kang (Journal of Cleaner Production, 2024)

Reduced moisture caused by short-term grazing prohibition results in a significant decrease of fungi abundance - Hongbin Zhao; Xiaofu Zhang; Huiyan Liu; Xue Bai; Jiaming Nie; Guodong Han; Bing Han (Journal of Arid Environments, 2024)

An intelligent control method for PEMFC air supply subsystem to optimize dynamic response performance - Qingqing Su; Jiaming Zhou; Fengyan Yi; Donghai Hu; Dagang Lu; Guangping Wu; Caizhi Zhang; Bo Deng; Deming Cao (Fuel, 2024)

Effect of Yamadazyma triangularis derived peptide XHY69AP on muscle fatigue via regulation of AMPK/PGC-1α and Nrf2/Keap1 pathways - Jiaming Cai; Ye Tao; Lujuan Xing; Lei Zhou; Ming Ju; Wangang Zhang (Food Bioscience, 2024)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Hyporheic exchange in a compound channel under unsteady flow: Numerical simulations - Jiaming Liu; Yang Xiao; Pei Xin; Nairu Wang; Saiyu Yuan; Taotao Zhang; Chentao Li; Carlo Gualtieri (Journal of Hydrology, 2024)

Cavity effects on spontaneous ignition of pressurized hydrogen jets - Jiaxin Zhang; Jiaming Huang; Qingxin Ba; Bo Zhou; David M. Christopher; Ming Gao; Xuefang Li (Fuel, 2024)

Effects of ultrasound-assisted emulsification and carboxymethyl cellulose addition on the rheological and microstructure properties of myofibrillar protein-soybean oil emulsion gel - Lei Zhou; Dacheng Kang; Jingyu Wang; Jiaming Cai; Lujuan Xing; Wangang Zhang (Food and Bioproducts Processing, 2024)

Image-guided structure-constrained inversion of electrical resistivity data for improving contaminations characterization - Xinmin Ma; Jieyi Zhou; Jing Li; Jiaming Zhang; Chunmei Han; Lili Guo; Shupeng Li; Deqiang Mao (Computers & Geosciences, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Distribution patterns and influential factors of pathogenic bacteria in freshwater aquaculture sediments - Wenxiang Xi; Xun Zhang; Xianbin Zhu; Jiaming Wang; Han Xue; Hongzhong Pan (Environmental Science and Pollution Research, 2024)

A novel forestry information-collecting mobile system - Shun Yao; Jiaming Zhang; Jiangming Kan; Ruifang Dong (Computers and Electronics in Agriculture, 2024)

Research on anode pressure control and dynamic performance of proton-exchange membrane fuel cell system for vehicular application - Heng Wei; Changqing Du; Xingyi Li; Chenxu Shi; Jiaming Zhang (Fuel, 2024)

Heterologous expression of protein-glutaminase in Escherichia coli Nissle 1917 for improved flavor properties of soy protein and its implications on high-moisture extrudates - Jiaming Li; Xinwen Zhang; Shijun Luo; Xinhong Wu; Guoqiang Zhang; Jianghua Li; Xiao Liu (Food Bioscience, 2024)

Effects of soybean endogenous enzyme hydrolysis on the quality of soymilk after blanching - Feng Yan; Shisheng Tong; Jiaming Zhang; Yuanyuan Zhao; Ping Liu (Food Bioscience, 2024)

Energetic characteristics of highly reactive Si nanoparticles prepared by magnesiothermic reduction of mesoporous SiO2 - Xinwen Ma; Weiduo Fei; Jiaming Liu; Xiandie Zhang; Jie Ji; Xiang Zhou (Chemical Engineering Journal, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Kinetic modeling and mechanisms of parahalogenated phenols degradation by UV222/H2O2 - Min Zhao; Ting Li; Yizhan Zhang; Jiaming Gan; Yiting Zhao; Xin Yu; Lei Wang (Journal of Cleaner Production, 2024)

Cas-Rainbow: Cas12a-driven single-reaction multiplex detection system - Yuqing Zhu; Jianming Zhou; Yuxin Liang; Yao Lu; Shujun Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2024)

An image-based system for locating pruning points in apple trees using instance segmentation and RGB-D images - Siyuan Tong; Jiaming Zhang; Wenbin Li; Yaxiong Wang; Feng Kang (Biosystems Engineering, 2023)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Effects of dietary vitamin E supplementation on growth performance, slaughter performance, antioxidant capacity and meat quality characteristics of finishing bulls - Jiaming Luan; Yinghai Jin; Tai Zhang; Xin Feng; Kai Geng; Min Zhang; Chunyin Geng (Meat Science, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

A shining transmutation of lignin into multicolor carbon dots via the dynamic solvent-fractionation engineering - Xinyan Hou; Jikun Xu; Pengfei Zhou; Lin Dai; Jiaming Zhang; Xiao Xiao; Kaifu Huo (Chemical Engineering Journal, 2023)

Sulfidation of zero-valent iron for enhanced reduction of chlorinated contaminants: A review on the reactivity, selectivity, and interference resistance - Jiaming Guo; Feilong Gao; Chengfang Zhang; Shakeel Ahmad; Jingchun Tang (Chemical Engineering Journal, 2023)

Regional Modeling of the Lithospheric Magnetic Field from Local and Satellite Constraints: A Case Study of the Xinjiang Region - Yan Feng; Jiaxuan Zhang; Shengqing Xiong; JinYuan Zhang; Jiaming Ou; Shuang Liu; Yijun Li; Ya Huang (Pure and Applied Geophysics, 2023)

A novel fish CRADD inhibits Singapore grouper iridovirus (SGIV) infection by mediating apoptosis and modulating SGIV CARD (VP48)-caspase-2 interaction - Xin Zhang; Siting Wu; Zetian Liu; Jiaming Liao; Jingguang Wei; Qiwei Qin (Aquaculture, 2023)

Microseismic monitoring and experimental study on rockburst in water-rich area of tunnel - Shibin Tang; Jiaming Li; Liexian Tang; Leitao Zhang (Tunnelling and Underground Space Technology, 2023)

Spatiotemporal distribution of phytoplankton community structure and its relationship with environmental factors in Hongze Lake, China - Jiahui Shi; Lixiao Ni; Jiaming Liu; Chen Xu; Jianhua Zhang; Xuqing Chen (Urban Climate, 2023)

Revealing the spatio-temporal characteristics and impact mechanism of carbon emission in China's urban agglomerations - Ziyi Wang; Jingxiang Zhang; Pingjia Luo; Dongqi Sun; Jiaming Li (Urban Climate, 2023)

Analysis of variation characteristics, transport paths, and influencing factors of atmospheric NO2 pollution in Western Europe - Jiaming Zhang; Tianzhen Ju; Bingnan Li; Chunxue Li; Jinyang Wang; Xuhui Xia; Xiaowen Niu (Environmental Monitoring and Assessment, 2023)

Electro-enhanced metal-free peroxymonosulfate activator coupled with membrane-assisted process for simultaneous Ni-EDTA decomplexation and Ni ions recovery - Jiaming Zhang; Chao Yu; Longqian Xu; Zhenyu Zhao; Deli Wu (Chemosphere, 2023)

A multi-scale experiment analysis of air entrainment and heat exhaust coefficient under lateral smoke exhaust in tunnel fires - Qiulin Liu; Zhisheng Xu; Chuangang Fan; Xiaochun Zhang; Jiaming Zhao; Houlin Ying; Haowen Tao (Tunnelling and Underground Space Technology, 2023)

Ship longitudinal stabilization control based on CGSA and nonlinear switch modification - Jiaming Fan; Xianku Zhang; Tian Cao; Daocheng Ma (Ocean Engineering, 2023)

Biological treatment as a green approach for enhancing electrochemical performance of wood derived carbon based supercapacitor electrodes - Jiaming Cao; Lin Lin; Jian Zhang; Feng Zhao; Junyou Shi; Fachun Guan; Dongliang Wang (Journal of Cleaner Production, 2023)

Zwitterionic loose polyamide nanofiltration membrane with good antifouling properties for efficient removal of humic acid and dyes - Chengbao Geng; Fangbo Zhao; Hongyan Niu; Jiaming Zhang; Yang Liu; Lijia Liu; Hongxing Dong; Zhiguo Li; Hongxu Chen (Journal of Environmental Chemical Engineering, 2023)

Identification of hepatoprotective peptides from porcine liver and its interaction with ethanol metabolizing enzymes in vitro - Zixu Wang; Lujuan Xing; Jiaming Cai; Fidel Toldrá; Yuejing Hao; Wangang Zhang (Food Bioscience, 2023)

Isolation and identification of a megalocytivirus strain (SKIV-TJ) from cultured spotted knifejaw (Oplegnathus punctatus) in China and its pathogenicity analysis - Jiaming Liao; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2023)

Experimental study on the characteristics of radiation floor cooling system based on an earth–air heat exchanger - Jiaming Yang; Wei Song; Houan Zhang; Jing Wang; Jiankai Dong (Energy and Buildings, 2023)

Catalytic degradation of bisphenol a (BPA) in water by immobilizing silver-loaded graphene oxide (GO-Ag) in ultrafiltration membrane with finger-like structure - Ye Yang; Fangbo Zhao; Liu Yang; Jiaming Zhang; Hee-Deung Park; Zhiguo Li; Hongxu Chen; Ximeng Zhang; Mingjin Gao (Chemical Engineering Journal, 2023)

A dual amplification-based CRISPR/Cas12a biosensor for sensitive detection of miRNA in prostate cancer - Yuqing Zhu; Xiaohe Zheng; Shujun Zhou; Wenjing Xiao; Xiaorui Sun; Jianming Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Analytica Chimica Acta, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Spatial and temporal distribution of absorbing aerosols in sub-Saharan Africa and GTWR model analysis - Chunxue Li; Tianzhen Ju; Bingnan Li; Jiaming Zhang; Jinyang Wang; Xuhui Xia; Shengtong Lei (Air Quality, Atmosphere & Health, 2023)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Tetrabromobisphenol A transformation by biochar supported post-sulfidated nanoscale zero-valent iron: Mechanistic insights from shell control and solvent kinetic isotope effects - Feilong Gao; Mingyi Zhang; Shakeel Ahmad; Jiaming Guo; Yinghao Shi; Xinzuo Yang; Jingchun Tang (Journal of Hazardous Materials, 2023)

Development of geopolymer-based composites for geothermal energy applications - Linfeng Zhang; Yingfan Wang; Boyin Ding; Jiaming Gu; Neven Ukrainczyk; Jingming Cai (Journal of Cleaner Production, 2023)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

Influence of hemin on structure and emulsifying properties of soybean protein isolate - Jiaming Zhang; Yangyang Jia; Wenjin Wu; Yingying Zhang; Ping Chen; Xiaofang Li; Xuetuan Wei; Chunmei Li; Kaikai Li (Food Chemistry, 2023)

Analysis of Remote Sensing Monitoring of Atmospheric Ozone in Japan from 2010 to 2021 - Shengtong Lei; Tianzhen Ju; Bingnan Li; Xuhui Xia; Cheng Huang; Jiaming Zhang; Chunxue Li (Water, Air, & Soil Pollution, 2023)

Degradation and dechlorination of trichloroacetic acid induced by an in situ 222 nm KrCl* excimer radiation - Jiaming Gan; Ting Zhu; Yizhan Zhang; Dailin Li; Ting Li; Min Zhao; ZengXia Zhao; Lei Wang (Chemosphere, 2023)

Potassium assisted pyrolysis of Chinese Baijiu distillers' grains to prepare biochar as controlled-release K fertilizer - Jiali Cheng; Jiaming Zhang; Xiao Xiao; Yue Yuan; Xuepin Liao; Bi Shi; Suyi Zhang (Science of The Total Environment, 2023)

Fibrillation of whey protein isolate by radio frequency heating for process efficiency: Assembly behavior, structural characteristics, and in-vitro digestion - Shuangshuang Wang; Yuxia Xie; Yi Ding; Zhenquan Huo; Jiaming Li; Jiaqing Song; Yucui Huo; Lili Zhao; Jing Zhang; Shaojin Wang; Jiaying Zhang; Wupeng Ge (Innovative Food Science & Emerging Technologies, 2023)

Enhancement of sodium salty taste modulate by protease-hydrolyzed Gum Arabic - Kailin Ye; Jiaming Qi; Yang Zhang; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2023)

Analysis on the Influencing Factors and Future Trend of HCHO Pollution in Brazil - Cheng Huang; Tianzhen Ju; Bingnan Li; Jinyang Wang; Jiaming Zhang; Shengtong Lei; Chunxue Li (Water, Air, & Soil Pollution, 2023)

The Intensification of Prolonged Cooling Climate-Exacerbated Late Ordovician–Early Silurian Mass Extinction: A Case Study from the Wufeng Formation–Longmaxi Formation in the Sichuan Basin - Zhibo Zhang; Yinghai Guo; Hengye Wei; Chunlin Zeng; Jiaming Zhang; Difei Zhao (Journal of Marine Science and Engineering, 2023)
The Late Ordovician–Early Silurian period was a significant transitional phase in geological history and has garnered global interest. This study focuses on the black shale series of the Wufeng Formation–Longmaxi Formation of the Upper Ordovician–Lower Silurian period in the Sichuan Basin. Based on the logging curves and lithological characteristics of the Yucan-1 Well, 46 black shale samples were collected from the target layer section for clay mineral XRD (46 samples) analysis and whole-rock XRF (14 samples) analysis. The results indicate that three third-order sequences (SQ1, SQ2, and SQ3) are present in the Wufeng Formation–Longmaxi Formation of the Yucan-1 Well, and two subfacies and three microfacies were identified. In conjunction with the characteristics as well as the characteristic parameters of whole-rock oxide and clay mineral content ((I/C), (S + I/S)/(I + C), CIA, CIA-error, CIW, PIA, MAP, and LST), the Wufeng Formation–Longmaxi Formation of the Yucan-1 Well is divided into three intervals. Interval I is the Wufeng Formation. During this interval, weathering intensity, surface temperature, and precipitation gradually decreased, while the climate shifted from warm and humid to cold and dry. This corresponds to two pulse-type biological extinction events and represents an interval of increasing organic carbon burial. Interval II encompasses the bottom-middle part of the Longmaxi Formation. Weathering intensity, surface temperature, and precipitation were characterized by smooth, low values. Subsequently, the climate was predominantly cold and dry. This was the primary interval of organic carbon enrichment. Interval III extends from the upper part to the top of the Longmaxi Formation. Weathering intensity, surface temperature, and precipitation gradually increased. The climate transitioned from cold and dry to warm and humid. Organic carbon burial gradually decreased, while sea levels dropped. This indicates that climate cooling was the primary controlling factor for this biological extinction event. In combination with previous divisions of graptolite zones in the Yucan-1 Well, it is postulated that this biological extinction event may primarily have been pulse extinction. The continuous cooling of the climate in the later period led to the continuous extinction of organisms that survived the disaster. Until approximately 438.76 Ma at the top of the Longmaxi Formation, the climate environment recovered to pre-extinction conditions, with a transition to a warm and humid climate again.

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Establishment and characterization of a brain tissue cell line from spotted knifejaw ( Oplegnathus punctatus ) and its susceptibility to several fish viruses - Jiaming Liao; Xin Zhang; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Journal of Fish Diseases, 2023)
Cells are important in the study of virus isolation and identification, viral pathogenic mechanisms and antiviral immunity. The spotted knifejaw ( Oplegnathus punctatus ) is a significant farmed fish in China that has been greatly affected by diseases in recent years. In this study, a new cell line derived from the spotted knifejaw brain (SKB) was established and characterized. SKB cells multiplied well in Leibovitz's L‐15 medium supplemented with 10% fetal bovine serum at 28°C. Chromosome analysis revealed that modal chromosome number was 48 for SKB. SKB cells exhibit susceptibility to several fish viruses, such as a largemouth bass virus, red grouper nervous necrosis virus (RGNNV), infectious spleen and kidney necrosis virus (ISKNV), Singapore grouper iridovirus (SGIV) and spotted knifejaw iridovirus isolate (SKIV‐TJ), as shown by cytopathic effect and increased viral titers. Electron microscopy results showed that the cytoplasm contained a large number of vacuoles, and many virus particles existed at the edge of the vacuoles in RGNNV‐infected cells and numerous viral particles were scattered throughout the cytoplasm in both ISKNV‐ and SKIV‐TJ‐infected cells. These results suggest that SKB is an ideal tool for studying host–virus interactions and potential vaccine development.

Detection and characterization of microplastics in the human testis and semen - Qiancheng Zhao; Long Zhu; Jiaming Weng; Zirun Jin; Yalei Cao; Hui Jiang; Zhe Zhang (Science of The Total Environment, 2023)

Superiority of UV222 radiation by in situ aquatic electrode KrCl excimer in disinfecting waterborne pathogens: Mechanism and efficacy - Ting Li; Yizhan Zhang; Jiaming Gan; Xin Yu; Lei Wang (Journal of Hazardous Materials, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

Magnetic nanometer combined with microwave: Novel rapid thawing promotes phenolics release in frozen-storage lychee - Canhua Xu; Jiaming Lu; Qingzhu Zeng; Junjia Zhang; Lihong Dong; Fei Huang; Yingbin Shen; Dongxiao Su (Food Chemistry, 2023)

Effects of carboxymethyl cellulose on the emulsifying, gel and digestive properties of myofibrillar protein-soybean oil emulsion - Lei Zhou; Jinyuan Jiang; Fan Feng; Jingyu Wang; Jiaming Cai; Lujuan Xing; Guanghong Zhou; Wangang Zhang (Carbohydrate Polymers, 2023)

The role of the joint capsule in the stability of the elbow joint - Fang Wang; Hao Wang; Mingxin Li; Shuoqi Jia; Jiaming Wang; Jianguo Zhang; Yubo Fan (Medical & Biological Engineering & Computing, 2023)

Effect of gastrodin against cognitive impairment and neurodegeneration in APP/PS1 mice via regulating gut microbiota–gut–brain axis - Yuhe Zhang; Yan Chen; Shushu Yuan; Qingxia Yu; Jianjiong Fu; Luyun Chen; Jiaming Liu; Yuping He (Experimental Brain Research, 2023)

From black water to flushing water: potential applications of chlorine-mediated indirect electrooxidation for ammonia removal - Shanshan Liu; Longqian Xu; Xiaoqing Lin; Jiaming Zhang; Deli Wu (Environmental Science and Pollution Research, 2023)

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

Global-aware siamese network for change detection on remote sensing images - Ruiqian Zhang; Hanchao Zhang; Xiaogang Ning; Xiao Huang; Jiaming Wang; Wei Cui (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Hollow 1D carbon tube core anchored in Co3O4@SnS2 multiple shells for constructing binder-free electrodes of flexible supercapacitors - Jiaming Wang; Ying Huang; Xianping Du; Shuai Zhang; Meng Zong (Chemical Engineering Journal, 2023)

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Depth-dependent drivers of soil aggregate carbon across Tibetan alpine grasslands - Junxiao Pan; Jiawei Shi; Dashuan Tian; Ruiyang Zhang; Yang Li; Yunlong He; Lei Song; Song Wang; Yicheng He; Jiaming Yang; Chunxue Wei; Shuli Niu; et al. (Science of The Total Environment, 2023)

Dynamic response of single-bucket foundation in clay under vertical variable amplitude cyclic loadings - Hailei Kou; Weiwei Fang; Nan Zhou; Jiaming Huang; Xixin Zhang (Ocean Engineering, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

Novel insights into Co synergy and electron-transfer pathways during the oxidation of contaminants by Cu-OOSO3- in CuCo2Ox/peroxymonosulfate system - Lele Zhao; Jiaming Zhang; Yuan Zong; Jun Ma; Chengying Bai; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2023)

Light use efficiency models incorporating diffuse radiation impacts for simulating terrestrial ecosystem gross primary productivity: A global comparison - Hang Xu; Zhiqiang Zhang; Xiaoyun Wu; Jiaming Wan (Agricultural and Forest Meteorology, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Self-repairing thermal energy storage gels demonstrating superior thermophysical properties and wearability towards personal thermal management in static and dynamic modes - Yingying Luo; Hongjiao Wu; Junpeng Qiao; Jiaming Zhang; Kai Liu; Liqing Zou; Ying Chen; Pengcheng Lin (Chemical Engineering Journal, 2023)

Highly efficient removal of hexavalent chromium from electroplating wastewater by ferrous/ferric hydroxide complex: From lab-scale to pilot-scale study - Xiaoqing Lin; Longqian Xu; Zhenyu Zhao; Shanshan Liu; Jiaming Zhang; Deli Wu (Chemical Engineering Journal, 2023)

Self-healing, reprocessable, degradable, thermadapt shape memory multifunctional polymers based on dynamic imine bonds and their application in nondestructively recyclable carbon fiber composites - Xiaohong Liu; Ending Zhang; Jiaming Liu; Jingjing Qin; Mengqin Wu; Chaolong Yang; Liyan Liang (Chemical Engineering Journal, 2023)

Effects of leaf scorch on chlorophyll fluorescence characteristics of walnut leaves - ChangJie Xing; ShiWei Wang; CuiFang Zhang; Tong Guo; HongLong Hao; ZhuoYa Zhang; Sheng Wang; JiaMing Shu (Journal of Plant Diseases and Protection, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

A sustainable development pattern integrating data centers and pasture-based agrivoltaic systems for ecologically fragile areas - Jiaming Zhang; Tao Wang; Yuan Chang; Bingsheng Liu (Resources, Conservation and Recycling, 2023)

Excess pore water pressure and seepage in slopes induced by breaking internal solitary waves - Zhuangcai Tian; Lei Jia; Jiaming Xiang; Guotao Yuan; Kun Yang; Jun Wei; Mingwei Zhang; Honglei Shen; Jianhua Yue (Ocean Engineering, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant - Zhuo Sun; Jiaming Zhang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Guoyou Nong; Mengqi Luo; Jue Wang (Journal of Environmental Management, 2023)

Analysis and intervention of heatwave related economic loss: Comprehensive insights from supply, demand, and public expenditure into the relationship between the influencing factors - Peng Wang; Wendi Zhang; Jiawen Liu; Pan He; Jiaming Wang; Lei Huang; Bing Zhang (Journal of Environmental Management, 2023)

Chlorine dioxide bleaching wastewater degradation in intimately coupled photocatalysis and functional bacteria: The roles of adsorption, photocatalysis, and biotransformation - Yinna Liang; Maman Galandi Abdoulaye; Chenxu Zhou; Bing Xiao; Jiaming Zhang; Jianhua Xiong; Qifeng Yang; J.R. Zhao; Shuangfei Wang (Journal of Cleaner Production, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Reinforcing strategies of CFRP plate for coped steel beams against local buckling - Chi Chiu Lam; Yufei Zhang; Jiaming Gu; Jingming Cai (Engineering Structures, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

TP-DDI: A Two-Pathway Deep Neural Network for Drug–Drug Interaction Prediction - Jiang Xie; Chang Zhao; Jiaming Ouyang; Hongjian He; Dingkai Huang; Mengjiao Liu; Jiao Wang; Wenjun Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

The Impact of Scour on Laterally Loaded Piles Bored and Socketed in Marine Clay - Chentao Li; Yang Xiao; Jieqing Liu; Qingwei Lin; Taotao Zhang; Jiaming Liu (Journal of Marine Science and Engineering, 2022)
The majority of long-span bridges and offshore construction in deep water are supported by bored pile foundations. Pile foundations under water will be susceptible to scour, which will pose a significant danger to their safe operation. A three-dimensional finite element (FE) numerical analysis was conducted to examine the influence of scour on the responses of laterally loaded drilled piles in marine clays. First, the FE numerical model was calibrated using field test data of a drilled pile that did not include scour in soft marine clay. The findings of numerical modeling reveal that scour decreases the ultimate lateral capacity of socketed drilled piles, with the percentage of reduction being strongly related to scour types and depth, but moderately related to scour hole width and slope angle. Finally, a semi-empirical formula for calculating the effects of scour on the lateral capacity of socketed drilled piles following scour is presented. This method may be utilized fast and effectively to calculate scour’s effects.

The influence of water-stress loading sequences on the creep behavior of granite - Shibin Tang; Jiaming Li; Shun Ding; Leitao Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Occurrence and driving forces of different nitrogen forms in the sediments of the grass and algae-type zones of Taihu Lake - Zihan Zhao; Mingli Zhang; Jiaming Tian; Kangkang Yu; Yan Chen; Yanhua Wang (Environmental Science and Pollution Research, 2022)

Relative importance of branching enzyme isoforms in determining starch fine structure and physicochemical properties of indica rice - Piengtawan Tappiban; Yaqi Hu; Jiaming Deng; Jiajia Zhao; Yining Ying; Zhongwei Zhang; Feifei Xu; Jinsong Bao (Plant Molecular Biology, 2022)

Characteristics of a rapid landsliding area along Jinsha River revealed by multi-temporal remote sensing and its risks to Sichuan-Tibet railway - Jiaming Yao; Hengxing Lan; Langping Li; Yiming Cao; Yuming Wu; Yixing Zhang; Chaodong Zhou (Landslides, 2022)

Consistency correction of echo intensity data for multiple radar systems and its application in quantitative estimation of typhoon precipitation - Shuai Zhang; Jing Han; Bingke Zhao; Zhigang Chu; Jie Tang; Limin Lin; Xiaoqin Lu; Jiaming Yan (Frontiers of Earth Science, 2022)

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Phosphorylation of CRMP2 by Cdk5 Negatively Regulates the Surface Delivery and Synaptic Function of AMPA Receptors - Longfei Cheng; Keen Chen; Jiong Li; Jiaming Wu; Jiaqi Zhang; Li Chen; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

Single-stranded DNA generated by high temperature accepts protons and builds up mutagenic and carcinogenic strong acids - Yuhan Lin; Xiaoxiao Zhang; Yuchuan Wang; Jiaming Zhang; Qiuyun Liu (Molecular Biology Reports, 2021)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Diverse transcriptional patterns of homoeologous recombinant transcripts in triploid fish (Cyprinidae) - Li Ren; Xueyin Zhang; Jiaming Li; Xiaojing Yan; Xin Gao; Jialin Cui; Chenchen Tang; Shaojun Liu (Science China Life Sciences, 2021)

Role of rgsA in Oxidative Stress Resistance in Pseudomonas aeruginosa - Shuyi Hou; Jiaqin Zhang; Xiaobo Ma; Qiang Hong; Lili Fang; Gangsen Zheng; Jiaming Huang; Yingchun Gao; Qiaoli Xu; Xinguo Zhuang; Xiuyu Song (Current Microbiology, 2021)

Failure mechanism of a slow-moving landslide on September 27, 2020, in Chang Nong Village, Guangxi, China - Jiaming Zhang; Zhi Zhou; Feng Lin; Qinggang Yang; Yi Luo (Landslides, 2021)

SMAD4 mutations and cross-talk between TGF-β/IFNγ signaling accelerate rates of DNA damage and cellular senescence, resulting in a segmental progeroid syndrome—the Myhre syndrome - Renuka Kandhaya-Pillai; Deyin Hou; Jiaming Zhang; Xiaomeng Yang; Goli Compoginis; Takayasu Mori; Tamara Tchkonia; George M. Martin; Fuki M. Hisama; James L. Kirkland; Junko Oshima (GeroScience, 2021)

Maneuverability and Hydrodynamics of a Tethered Underwater Robot Based on Mixing Grid Technique - Jiaming Wu; Shunyuan Xu; Hua Liao; Chenghua Ma; Xianyuan Yang; Haotian Wang; Tian Zhang; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
The maneuverability and hydrodynamic performance of the tethered underwater robot in a uniform flow field is investigated. In this research, a tethered underwater robot symmetrically installed with NACA66 hydrofoils and Ka 4-70/19A ducted propellers around its main body is first constructed. The method of overlapping grid combined with sliding mesh is applied in the numerical simulations, and the principle of relative motion is adopted to describe the hydrodynamic responses of the tethered underwater robot during the robot manipulation. The reliability of the CFD methods applied in this research is verified by experimental results, and the comparison between numerical and experimental ones shows that there is very little difference being found. The numerical results indicate that computational cost due to the research’s large-scale domain can be effectively reduced by the adopted numerical methods, hydrofoils’ control effect is greatly influenced by the towing speeds, and thrusts issued from the ducted propellers are related to the tethered underwater robot’s position and towing speed.

Research on the rainfall-induced regional slope failures along the Yangtze River of Anhui, China - Jiaming Zhang; Yi Luo; Zhi Zhou; Chikhotkin Victor; Modong Duan (Landslides, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

Gene polymorphism of chalcone isomerase influence the accumulation of flavonoids in licorice (Glycyrrhiza spp.) - Xiaodong Zhang; Shaokai Tian; Lin Qi; Wendong Li; Jiaming Hou; Lin Yang; Zhixin Zhang; Ying Liu (Genetic Resources and Crop Evolution, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Large-Scale Test Model of the Progressive Deformation and Failure of Cracked Soil Slopes - Zhi Zhou; Jiaming Zhang; Fulong Ning; Yi Luo; Lily Chong; Kuangbiao Sun (Journal of Earth Science, 2020)

Canopy photosynthetic capacity drives contrasting age dynamics of resource use efficiencies between mature temperate evergreen and deciduous forests - Hang Xu; Jingfeng Xiao; Zhiqiang Zhang; Scott V. Ollinger; David Y. Hollinger; Yude Pan; Jiaming Wan (Global Change Biology, 2020)
Forest resource use efficiencies (RUEs) can vary with tree age, but the nature of these trends and their underlying mechanisms are not well understood. Understanding the age dynamics of forest RUEs and their drivers is vital for assessing the trade‐offs between forest functions and resource consumption, making rational management policy, and projecting ecosystem carbon dynamics. Here we used the FLUXNET2015 and AmeriFlux datasets and published literature to explore the age‐dependent variability of forest light use efficiency (LUE) and inherent water use efficiency as well as their main regulatory variables in temperate regions. Our results showed that evergreen forest RUEs initially increased before reaching the mature stage (i.e., around 90 years old), and then gradually declined; in contrast, RUEs continuously increased with age for mature deciduous forests. Changing canopy photosynthetic capacity ( A max ) was the primary cause of age‐related changes in RUEs across temperate forest sites. More importantly, soil nitrogen (N) increased in mature deciduous forests through time but decreased in older evergreen forests. The age‐dependent changes in soil N were closely linked with the age dynamics of A max for mature temperate forests. Additionally, soil nutrient conditions played a greater role in deciduous forest RUEs than evergreen forest RUEs. This study highlights the importance of stand age and forest type on temperate forest RUEs over the long term.

A Risk Assessment Method for Metro Shield Tunnel Construction Based on Interval Number - Yeqin Zhang; Jiaming Zhang; Hailin Guo; Yang Zhou; Guofu Ma; Cong Wang (Geotechnical and Geological Engineering, 2020)

A novel facial attractiveness evaluation system based on face shape, facial structure features and skin - Jian Zhao; Miao Zhang; Chen He; Xie Xie; Jiaming Li (Cognitive Neurodynamics, 2020)

Development and characterization of 33 SNP markers for the red-crowned crane (Grus japonensis) using a genotyping-by-sequencing approach - Nan Xu; Yining Chen; Jiaming Zhang; Qingzheng Zhang; Jing Yang; Jingjing Li; Hongyi Liu (Conservation Genetics Resources, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

CDKN1B Mediates Apoptosis of Neuronal Cells and Inflammation Induced by Oxyhemoglobin via miR-502-5p After Subarachnoid Hemorrhage - Dong Chen; Xianwei Wang; Jiaming Huang; Sifu Cui; Liqiang Zhang (Journal of Molecular Neuroscience, 2020)

Dynamic Analysis of the Rock Burst Potential of a Longwall Panel Intersecting with a Fault - Lishuai Jiang; Peng Kong; Peipeng Zhang; Jiaming Shu; Qingbiao Wang; Lianjun Chen; Quanlin Wu (Rock Mechanics and Rock Engineering, 2020)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)

De novo assembly, transcriptome characterization, and simple sequence repeat marker development in duckweed Lemna gibba - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Deguan Tan; Bingying Han; Xuepiao Sun; Jiaming Zhang (Physiology and Molecular Biology of Plants, 2020)

Mechanical and structural properties of radiation-damaged allanite-(Ce) and the effects of thermal annealing - Claudia E. Reissner; Ulrich Bismayer; Daniel Kern; Michael Reissner; Sulgiye Park; Jiaming Zhang; Rodney C. Ewing; Anna Shelyug; Alexandra Navrotsky; Carsten Paulmann; Radek Škoda; Lee A. Groat; et al. (Physics and Chemistry of Minerals, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Identification and classification of resource-based cities in China - Jianhui Yu; Jiaming Li; Wenzhong Zhang (Journal of Geographical Sciences, 2019)

Gene coexpression analysis reveals dose-dependent and type-specific networks responding to ionizing radiation in the aquatic model plant Lemna minor using public data - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Xuepiao Sun; Jiaming Zhang (Journal of Genetics, 2019)

Comparative morphology of in vivo and in vitro laticiferous cells and potential use of in vitro laticifers in early selection of rubber tree clones - Deguan Tan; Anuwat Kumpeangkeaw; Xuepiao Sun; Weiguo Li; Yiming Zhu; Jiaming Zhang (Trees, 2019)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Integrated control of tobacco black shank by combined use of riboflavin and Bacillus subtilis strain Tpb55 - Chengsheng Zhang; Jiaming Gao; Teng Han; Xueying Tian; Fenglong Wang (BioControl, 2017)

Study of physico-mechanical properties of Emeishan basalt saprolites in Yunnan, China - Zhe Ren; Luyue Zhang; Zemin Xu; Jiaming Zhang; Jipu Chen (Bulletin of Engineering Geology and the Environment, 2017)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Small RNA changes in synthetic Brassica napus - Ying Fu; Meili Xiao; Huasheng Yu; Annaliese S. Mason; Jiaming Yin; Jiana Li; Dongqing Zhang; Donghui Fu (Planta, 2016)

Chemical and isotopic constrains on the origin of brine and saline groundwater in Hetao plain, Inner Mongolia - Jun Liu; Zongyu Chen; Lijuan Wang; Yilong Zhang; Zhenghong Li; Jiaming Xu; Yurong Peng (Environmental Science and Pollution Research, 2016)

Genetic mapping and molecular marker development for Pi65(t), a novel broad-spectrum resistance gene to rice blast using next-generation sequencing - Wenjing Zheng; Yan Wang; Lili Wang; Zuobin Ma; Jiaming Zhao; Ping Wang; Lixia Zhang; Zhiheng Liu; Xiaochun Lu (Theoretical and Applied Genetics, 2016)

Rapid and highly efficient callus induction and plant regeneration in the starch-rich duckweed strains of Landoltia punctata - Meng Huang; Lili Fu; Xuepiao Sun; Rong Di; Jiaming Zhang (Acta Physiologiae Plantarum, 2016)

Stacking S5-n and f5-n to overcome sterility in indica–japonica hybrid rice - Jiaming Mi; Guangwei Li; Jianyan Huang; Huihui Yu; Fasong Zhou; Qifa Zhang; Yidan Ouyang; Tongmin Mou (Theoretical and Applied Genetics, 2016)

Industrial spatial agglomeration using distance-based approach in Beijing, China - Jiaming Li; Wenzhong Zhang; Jianhui Yu; Hongxia Chen (Chinese Geographical Science, 2015)

Chlorella thermophila (Trebouxiophyceae, Chlorophyta), a novel thermo-tolerant Chlorella species isolated from an occupied rooftop incubator - Shuai Ma; Bingyin Han; Volker A. R. Huss; Xiaowen Hu; Xuepiao Sun; Jiaming Zhang (Hydrobiologia, 2015)

Study on the synergy between intra-urban resident’s migration and job change in Beijing - Jianhui Yu; Guanpeng Dong; Wenzhong Zhang; Jiaming Li (Journal of Geographical Sciences, 2015)

Species distribution, genetic diversity and barcoding in the duckweed family (Lemnaceae) - Yaliang Xu; Shuai Ma; Meng Huang; Ming Peng; Manuela Bog; K. Sowjanya Sree; Klaus-J. Appenroth; Jiaming Zhang (Hydrobiologia, 2015)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

Age-dependent and jasmonic acid-induced laticifer-cell differentiation in anther callus cultures of rubber tree - Deguan Tan; Xuepiao Sun; Jiaming Zhang (Planta, 2014)

In vitro isolation and cultivation of human chondrocytes for osteoarthritis renovation - Jiaming Xu; Changqing Zhang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

Propofol Administration Modulates AQP-4 Expression and Brain Edema After Traumatic Brain Injury - Zhongyang Ding; Jiaming Zhang; Jinyu Xu; Guangjie Sheng; Guorong Huang (Cell Biochemistry and Biophysics, 2013)

A high resolution lithospheric magnetic field model over China - JiaMing Ou; AiMin Du; E. Thébault; WenYao Xu; XiaoBo Tian; TieLong Zhang (Science China Earth Sciences, 2013)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)

Production of cyclic adenosine monophosphate by Arthrobacter sp. A302 using fed-batch fermentation with pH-shift control - Jiaming Cao; Xiaochun Chen; Huajing Ren; Jindan Zhang; Lei Li; Yong Chen; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2012)

The Arg194Trp polymorphism in the XRCC1 gene and cancer risk in Chinese Mainland population: a meta-analysis - Jin Huang; Jie Zhang; Yuliang Zhao; Banghua Liao; Jiaming Liu; Ling Li; Mingheng Liao; Lanlan Wang (Molecular Biology Reports, 2011)

Histochemical and immunohistochemical identification of laticifer cells in callus cultures derived from anthers of Hevea brasiliensis - Deguan Tan; Xuepiao Sun; Jiaming Zhang (Plant Cell Reports, 2011)

Precise dating of abrupt shifts in the Asian Monsoon during the last deglaciation based on stalagmite data from Yamen Cave, Guizhou Province, China - Yan Yang; DaoXian Yuan; Hai Cheng; MeiLiang Zhang; JiaMing Qin; YuShi Lin; XiaoYan Zhu; R. Lawrence Edwards (Science China Earth Sciences, 2010)

Isolation and characterization of a novel EAR-motif-containing gene GmERF4 from soybean (Glycine max L.) - Gaiyun Zhang; Ming Chen; Xueping Chen; Zhaoshi Xu; Liancheng Li; Jiaming Guo; Youzhi Ma (Molecular Biology Reports, 2010)

Evaporite karst and resultant geohazards in China - Lu Yaoru; Zhang Feng’e; Qi Jixiang; Xu Jiaming; Guo Xiuhong (Carbonates and Evaporites, 2002)